ANALISIS KINERJA TURBIN SAVONIUS DOUBLE-STAGED DESAIN ROTOR HELICAL MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMICS - Nugraha Rafi Ramadhan (2021)
The vertical axis wind turbine is one of the most promising power generators on a household scale. This is based on its ability to work at low wind speeds. The Savonius turbine is one of several types of vertical axis wind turbines. The weakness of this turbine is its design which makes the flow is divided into negative and positive. Modification of the shape of the turbine rotor was also carried out where a Helical rotor type was developed which had better performance than the conventional savonius rotor. This research focuses on one of the modifications to the savonius Helical turbine where the addition of stage is carried out to determine whether there is an increase in turbine performance in the form of power coefficient and torque coefficient. The method used in this research is the Finite Volume Method with the help of Computational Fluid Dynamics Software. The speed values selected for this study were 2 m/s, 3 m/s, 5 m/s and 8 m/s, namely low wind speeds. The result of this research is that the addition of the Helical turbine stage is able to increase the peak power coefficient value by 78.30% and 48.68% for the peak torque coefficient value. This is due to the increase in the torque value for each speed variant in the Double-stage turbine. Based on the results of the study, it can be concluded that the addition of the number of stage affects the performance of the savonius Helical turbine.